2010
DOI: 10.1186/1746-6148-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with within-herd transmission of bovine leukemia virus on dairy farms in Japan

Abstract: BackgroundAlthough several attempts have been made to control enzootic bovine leukosis (EBL) at the local level, a nationwide control program has not been implemented in Japan, except for passive surveillance. Effective control of EBL requires that the transmission routes of bovine leukemia virus (BLV) infection should be identified and intercepted based on scientific evidence. In this cross-sectional study, we examined the risk factors associated with within-herd transmission of BLV on infected dairy farms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 15 publications
3
87
1
2
Order By: Relevance
“…The pertinent literature has reported viral particles and viral DNA in cows' milk or colostrum that could be considered a risk factor for transmission to calves [33][34][35][36]. Viral DNA was also detected in fresh milk in the present study, thereby agreeing with previous reports, despite not having been described as a risk factor for humans.…”
Section: Resultssupporting
confidence: 92%
“…The pertinent literature has reported viral particles and viral DNA in cows' milk or colostrum that could be considered a risk factor for transmission to calves [33][34][35][36]. Viral DNA was also detected in fresh milk in the present study, thereby agreeing with previous reports, despite not having been described as a risk factor for humans.…”
Section: Resultssupporting
confidence: 92%
“…In cats, both feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) are regarded as important risk factors for feline hemoplasma infections [6,7,14,30]. Although the reasons why feline retroviral infections are related to hemoplasma infections remain unclear, the routes of infection are thought to be the same [6].…”
Section: Discussionmentioning
confidence: 99%
“…Vertical transmission of BLV in cattle across the placenta or through colostrums has been previously reported [16]. Horizontal transmission of BLV has also been reported, which can occur with hematophagous insect bites or inappropriate medical treatment [12,14]. One report described the use of molecular techniques to show how hemoplasma could be transmitted vertically and horizontally in cattle [11].…”
Section: Discussionmentioning
confidence: 99%
“…These insects are known to be more abundant in southern regions of Japan with the horsefly a possible vector involved in the horizontal transmission of BLV. The presence of horseflies has been positively correlated to within-herd seroprevalence in Japan [11]. Furthermore, milk and colostrum from infected cattle can contain BLV-infected cells [4,6], although not all BLV-positive cattle produce milk containing BLV [23].…”
mentioning
confidence: 99%
“…However, housing systems were changed to a loose housing system leading up to 1990 with a free-stall barn system introduced into 50% of dairy farms breeding more than 75 heads [9]. Our recent study showed that a loose housing system was utilized in 23% of dairy herds and was a risk factor for transmission of BLV [11,18]. We believe that the increase in within-herd prevalence for dairy herds can be partially attributed to the change of housing systems over the last two decades, as it has enabled dairy cows to have greater contact with each other.…”
mentioning
confidence: 99%